Perancangan Sistem Informasi Institutional Respository Politeknik Enjinering Indoroma - Mulyani, Heti; Tiawan; Nugraha, Muhammad (Technomedia Journal, 2022)
Institutional Repository is one of the facilities needed by universities to access, store, publish scientific works of the academic community digitally, such as journal articles, e-books, student final project results and other scientific works. The method used to develop this repository application uses the Waterfall method which has a systematic information system development model and consists of stages of needs analysis, software prototype design, implementation, software testing to software maintenance. The software used in developing this repository application uses Dspace. The purpose of this research is to build an Institutional Repository application to support smart campuses, especially at the Indorama Engineering Polytechnic. Smart campus combines learning systems and data storage facilities with the use of information technology, smart campus has information technology facilities such as e-learning, campus website, e-library, institutional repository and various other information services. The results of this study are in the form of an institutional repository application that can be used by all academics, both within the Indorama Engineering Polytechnic and the wider community. Keywords: Institutional Repository, Smart Campus, Dspace, Scientific Works, Waterfall.